The Financial Performance of Regional Government on Capital Expenditure - Jouzar Farouq Ishak; Sudradjat Sudradjat; Muhammad Umar Mai (JURNAL RISET TERAPAN AKUNTANSI, 2021)
This study aims to examine the impact the financial performance of regional government on capital expenditure allocation of Central Java Province. To meet such aim, we carried out a census techniques by taking all populations as a sample. The results suggest that there is one determinant of capital expenditure allocation, namely the degree of fiscal decentralization. This factor can be a solution to the problems of this study, namely the sub optimal allocation of capital expenditure. The locally-generated revenue contributes greatly to the total amount of revenue that can be generated by the region, reflect the greater ability of the region to implement decentralization activities that will eventually impact the allocation of capital expenditure. These findings provide a better understanding for government empirical evidence about the degree of decentralization, financial effectiveness, financial efficiency, and financial independence of the allocation of capital expenditure.